2009
DOI: 10.1016/j.febslet.2009.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of TRPV2 ion channel in the sensitivity of dystrophic muscle to eccentric contractions

Abstract: a b s t r a c tDuchenne myopathy is a lethal disease due to the absence of dystrophin, a cytoskeletal protein.Muscles from dystrophin-deficient mice (mdx) typically present an exaggerated susceptibility to eccentric work characterized by an important force drop and an increased membrane permeability consecutive to repeated lengthening contractions. The present study shows that mdx muscles are largely protected from eccentric work-induced damage by overexpressing a dominant negative mutant of TRPV2 ion channel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 54 publications
4
74
1
1
Order By: Relevance
“…TRPV2 expression has been observed in TRPV1-negative medium-to large-diameter neurons of the rat dorsal root and trigeminal ganglia and possibly in thinly myelinated nociceptors (Caterina et al, 1999;Lewinter et al, 2008). However, TRPV2 mRNA or immunoreactivity has also been detected in the brain, autonomic ganglia, spinal cord, skeletal and vascular myocytes, visceral organs (including the intestine, pancreas, spleen, and bladder), and blood cells (Caterina et al, 1999;Ichikawa and Sugimoto, 2001;Muraki et al, 2003;Kashiba et al, 2004;Lewinter et al, 2004;Inada et al, 2006;Lewinter et al, 2008;Hisanaga et al, 2009;Zanou et al, 2009;Link et al, 2010). TRPV2 expression may also be involved in the migration and proliferation of cancer cells (Caprodossi et al, 2008;Monet et al, 2010), and TRPV2-positive neurons observed in the rat myenteric plexus may be IPANs (Kashiba et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…TRPV2 expression has been observed in TRPV1-negative medium-to large-diameter neurons of the rat dorsal root and trigeminal ganglia and possibly in thinly myelinated nociceptors (Caterina et al, 1999;Lewinter et al, 2008). However, TRPV2 mRNA or immunoreactivity has also been detected in the brain, autonomic ganglia, spinal cord, skeletal and vascular myocytes, visceral organs (including the intestine, pancreas, spleen, and bladder), and blood cells (Caterina et al, 1999;Ichikawa and Sugimoto, 2001;Muraki et al, 2003;Kashiba et al, 2004;Lewinter et al, 2004;Inada et al, 2006;Lewinter et al, 2008;Hisanaga et al, 2009;Zanou et al, 2009;Link et al, 2010). TRPV2 expression may also be involved in the migration and proliferation of cancer cells (Caprodossi et al, 2008;Monet et al, 2010), and TRPV2-positive neurons observed in the rat myenteric plexus may be IPANs (Kashiba et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, mdx muscles were largely protected from eccentric work-induced force drop by the same transgenic strategy (Zanou et al, 2009). These results suggest that the entry of Ca 2+ through TRPV2 channels precedes and is involved in membrane damage.…”
Section: Fig 3 Production Of a Dominant-negative (Dn) Trpv2 Mutantmentioning
confidence: 99%
“…Duchenne myopathy is a lethal disease due to the absence of dystrophin, a cytoskeletal protein (Zanou et al, 2009). Prognosis Muscles from dystrophin-deficient mice are largely protected from eccentric work-induced damage by overexpressing a dominant negative mutant of TRPV2 ion channel.…”
Section: Diseasementioning
confidence: 99%
“…Note Mechanisms: TRPV2 is a principal Ca(2+)-entry route leading to a sustained [Ca(2+)](i) increase and muscle degeneration (Zanou et al, 2009). Disease When transgenic mice expressing a TRPV2 mutant in muscle are crossed with mdx mice, the [Ca(2+)](i) increase in muscle fibers is reduced by dominantnegative inhibition of endogenous TRPV2 .…”
Section: Muscular Dystrophymentioning
confidence: 99%
See 1 more Smart Citation